PELAKSANAAN KETENTUAN PASAL 24 PERATURAN DAERAH KOTA PONTIANAK NOMOR 12 TAHUN 2021 TENTANG PENGELOLAAN SAMPAH - NIM. A1011181242, RIZKA SULISTIA AMANDA (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Provisions regarding the prohibition of littering are contained in Law Number 18 of 2008 concerning Waste Management. Article 29 Paragraph 1 letter e emphasizes that every person is prohibited from throwing rubbish not in the designated and provided place. Pontianak City Regional Regulation Number 12 of 2021 is stipulated in the framework of a good and healthy environment which is a human right of every Indonesian citizen as mandated in Article 28 H of the 1945 Constitution of the Republic of Indonesia.Empirical legal research is oriented to primary data (results of research in the field). Empirical legal research is an approach carried out by field research by looking at and observing what happens in the field, the application of these regulations in practice in society. To support this empirical research, normative research with a statutory approach was also used by reviewing statutory regulations related to the Implementation of the Provisions of Article 24 of Pontianak City Regional Regulation Number 12 of 2021 concerning Waste Management (Study in Pontianak City). Pontianak City Government through The Pontianak City Environmental Service (DLH) has prepared several efforts to deal with the increasing volume of waste. Head of the Pontianak City DLH, Syarif Usmulyono, said that in dealing with the increasing volume of waste, his party was forced to increase the waste transportation routine to then be disposed of directly to the final disposal site (TPA) in Batu Layang. The 3R principle is certainly an effective way to manage waste so that the environment remains maintained, clean and healthy.Apart from that, the Pontianak City Environmental Service will improve its waste reduction performance at TPST/TPS3R/Trash Banks, both those owned by the government and those owned by the community.